Exploring the impact of a personalised disability reform on people with disability and their primary carers: Evidence from the Australian national disability insurance scheme - Bernice Hua Ma; Samia Badji; Gang Chen; Dennis Petrie (PLoS ONE, 2025)
Australia introduced the National Disability Insurance Scheme (NDIS) in 2013 to provide personalised formal care to individuals under 65 with significant and likely permanent disability. However, many ineligible individuals now face challenges accessing care. Against the backdrop of the introduction of NDIS funding and the simultaneous defunding of other disability services due to the NDIS, this research investigates the short-term impacts of NDIS on the formal service utilisation and carer outcomes for people with profound or severe disability, irrespective of their NDIS status. Using the staggered NDIS rollout, we analyse data from the 2015 and 2018 Survey of Disability, Ageing and Carers. We compare outcomes between primary carers and care recipients in NDIS-available areas (n = 736) and NDIS-not-yet-available areas (n = 318). Results show no short-term impact of NDIS availability on formal service utilisation or frequency, or primary carer outcomes. While some individuals benefit from the NDIS, others may lose access to care. Policymakers should address NDIS equity concerns and consider targeted measures to improve carer outcomes.